Christianization of Bulgaria and Great Moravia – parallelism of intentions - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2011)
The article is devoted to a comparison of the processes of Christianization in Bulgaria and Great Moravia in the ninth century. The author analyzes the political and cultural motivations behind the adoption of Christianity by both states and points to similarities in their paths toward integration with Christian Europe. The aim of the article is to demonstrate the common elements of the Christianization process in both countries and to examine their political significance. The author employs a comparative method, analyzing historical sources concerning Bulgaria and Great Moravia. The study demonstrates that the adoption of Christianity was not merely a religious act, but above all an element in the construction of statehood and the legitimation of power. Bulgarians and Moravians used Christianization to strengthen their international position and to participate in the culture of Christian Europe. The results of the analysis indicate that despite differing political conditions, both processes possessed a similar character and led to the lasting integration of these countries with either Byzantine or Latin civilization.